2017
DOI: 10.1080/02770903.2017.1373393
|View full text |Cite
|
Sign up to set email alerts
|

Improving the asthma disparity gap with legal advocacy? A qualitative study of patient-identified challenges to improve social and environmental factors that contribute to poorly controlled asthma

Abstract: Patients with poorly controlled asthma in a disadvantaged urban northeast community identified common barriers in both the domestic and work environments that impeded attainment of symptom control. These challenges may be best addressed through legal advocacy for those most at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…The landlord-related challenges reported by study participants may help explain the observed association between rentership and lower testing rates [17]. Renters face similar challenges with their landlords when addressing asthma triggers in their homes, including a lack of knowledge about tenant rights, lack of financial resources, and a fear of retribution [33]. Policy interventions may be necessary to address landlord-related barriers to well stewardship.…”
Section: Discussionmentioning
confidence: 92%
“…The landlord-related challenges reported by study participants may help explain the observed association between rentership and lower testing rates [17]. Renters face similar challenges with their landlords when addressing asthma triggers in their homes, including a lack of knowledge about tenant rights, lack of financial resources, and a fear of retribution [33]. Policy interventions may be necessary to address landlord-related barriers to well stewardship.…”
Section: Discussionmentioning
confidence: 92%
“…The landlord-related challenges reported by study participants may help explain the observed association between rentership and lower testing rates [17]. Renters face similar challenges with their landlords when addressing asthma triggers in their homes [33]. These challenges include a lack of knowledge about tenant rights, lack of financial resources, and a fear of retribution [33].…”
Section: Discussionmentioning
confidence: 96%
“…Renters face similar challenges with their landlords when addressing asthma triggers in their homes [33]. These challenges include a lack of knowledge about tenant rights, lack of financial resources, and a fear of retribution [33]. Policy interventions may be necessary to address landlord-related barriers to well stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have reported underutilization of workers' compensation insurance by injured workers, 29 fear of divulging PTSD symptoms by police after September 11, 30 patients' fear of retaliation after reporting work-related exacerbation of asthma, 31 and reluctance by coal miners to participate in a program to identify and track the progress of lung disease. 32 Investigating and developing CDS to help manage discussions about this and similar sensitive issues could help guide development of the most effective CDS for this purpose.…”
Section: Barriersmentioning
confidence: 99%